1999
DOI: 10.1046/j.1365-2362.1999.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein does not inhibit apoptosis in human hepatoma cells

Abstract: Thus, it is unlikely that hepatitis C virus core or E2 protein inhibit apoptosis mediated by apoptosis-signalling pathways sensitive to cytokine response modifier A protein. Discrepancies to previous reports probably reflect specific effects of hepatitis C virus core protein on different apoptotic pathways and/ or cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Coredependent inhibition of TNF-α- [71] and CD95Ligand-induced apoptosis [72] has been described in a hepatoma cell line. In other models, overexpressed HCV core protein did not prevent CD95Ligand-induced apoptosis in hepatoma cells [73] or transgenic mice expressing HCV core protein, E1, E2 and NS2, respectively. HCV core protein inhibits CD95Ligand-mediated apoptosis by prevention of cytochrome C release from mitochondria and consecutive activation of caspase-9, -3 and -7 [74] .…”
Section: Hcv Core Proteinmentioning
confidence: 88%
“…Coredependent inhibition of TNF-α- [71] and CD95Ligand-induced apoptosis [72] has been described in a hepatoma cell line. In other models, overexpressed HCV core protein did not prevent CD95Ligand-induced apoptosis in hepatoma cells [73] or transgenic mice expressing HCV core protein, E1, E2 and NS2, respectively. HCV core protein inhibits CD95Ligand-mediated apoptosis by prevention of cytochrome C release from mitochondria and consecutive activation of caspase-9, -3 and -7 [74] .…”
Section: Hcv Core Proteinmentioning
confidence: 88%
“…The hepatitis C virus (HCV) core protein is similarly localized (2,6,54). Moreover, expression of the HCV core protein causes apoptosis induction in some, but not all, transfected cells (6,25,29). The determinants of lipid droplet localization of the HCV core protein have been mapped to amphipathic ␣-helices whose primary sequence is homologous to plant oleosins, which associate with lipid droplets (30).…”
Section: Discussionmentioning
confidence: 99%
“…13 Dumoulin et al reported that HCV core protein or HCV E2 protein individually do not prevent TNF-␣ or Fas induced-apoptosis in transient transfected HepG2 cells. 14 Lasarte et al reported that a recombinant adenovirus encoding HCV core and E1 proteins protects liver cells from cytokine-induced hepatocellular damage in experimental models of TNF-mediated hepatic injury. 15 These data suggest the possibility that E1 with or without E2 has an antiapoptotic effect.…”
Section: Discussionmentioning
confidence: 99%